Comparing lung ultrasound with bioimpedance spectroscopy for evaluating hydration in peritoneal dialysis patients. (January 2015) - Paudel, Klara; Kausik, Tarun; Visser, Annemarie; Ramballi, Cheryl; Fan, Stanley L
Abstract Background Bioimpedance spectroscopy (BIS), ultrasound lung comets (ULC) and serum biomarkers (N‐terminal pro–brain natriuretic peptide, NT‐proBNP) have all been used to assist clinicians to determine hydration status in dialysis patients. Methods We performed simultaneous BIS, ULC and NT‐proBNP measurements in 27 peritoneal dialysis patients to determine the concordance of the three methods. Results Patients with evidence of increasing lung congestion (as determined by ultrasound) were more likely to be diabetic, have systolic hypertension and have higher NT‐proBNP (r = 0.65, P < 0.0005). Although there was a trend for patients with high ULC to be overhydrated as determined by BIS, this did not reach statistical significance. Moreover, the correlation between BIS and NT‐proBNP (though statistically significant at r = 0.47, P < 0.02) appeared to be weaker. Conclusion BIS and ULC may be complementary, providing different information, whereas BIS may be more specific to hydration. ULC and NT‐proBNP may indicate left ventricular failure coexisting with overhydration.